Salmonella Enteritidis bacteriophage candidates for phage therapy of poultry - Sillankorva, Sanna (2010)
Aims: Salmonella is a worldwide foodborne pathogen causing acute enteric infections in humans. In the recent years, the use of bacteriophages has been suggested as a possible tool to combat this zoonotic pathogen in poultry farms. This work aims to isolate and perform comparative studies of a group of phages active against a collection of specific Salmonella Enteritidis strains from Portugal and England. Also, suitable phage candidates for therapy of poultry will be selected. Methods and Results: The Salm. Enteritidis strains studied were shown to have a significantly high occurrence of defective (cryptic) prophages; however, no live phages were found in the strains. Bacteriophages isolated from different environments lysed all except one of the tested Salm. Enteritidis strains. The bacteriophages studied were divided into different groups according to their genetic homology, RFLP profiles and phenotypic features, and most of them showed no DNA homology with the bacterial hosts. The bacteriophage lytic efficacy proved to be highly dependent on the propagation host strain. Conclusions: Despite the evidences shown in this work that the Salm. Enteritidis strains used did not produce viable phages, we have confirmed that some phages, when grown on particular hosts, behaved as complexes of phages. This is most likely because of the presence of inactive phage-related genomes (or their parts) in the bacterial strains which are capable of being reactivated or which can recombine with lytic phages. Furthermore, changes of the bacterial hosts used for maintenance of phages must be avoided as these can drastically modify the parameters of the phage preparations, including host range and lytic activity. Significance and Impact of the Study: This work shows that the optimal host and growth conditions must be carefully studied and selected for the production of each bacteriophage candidate for animal therapy.